2016
DOI: 10.1016/j.jmb.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Tonic PKA Activity Regulates SK Channel Nanoclustering and Somatodendritic Distribution

Abstract: Small-conductance calcium-activated potassium (SK) channels mediate a potassium conductance in the brain and are involved in synaptic plasticity, learning, and memory. SK channels show a distinct subcellular localization that is crucial for their neuronal functions. However, the mechanisms that control this spatial distribution are unknown. We imaged SK channels labeled with fluorophore-tagged apamin and monitored SK channel nanoclustering at the single molecule level by combining atomic force microscopy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…5 A ; KT5720: μ = 20 ± 5.5 pN, surface density = 9.14 ± 1.02%, P < 0.01; Fig. 5 B ; Rp‐cAMPS: μ = 20 ± 5.0 pN, surface density = 10.09 ± 1.41%, F (2, 20) = 12.27, P < 0.01]; however, we did not observe any induction of nanoclustering of K Ca 2 channels, which we had previously found (12) and confirmed again here with K Ca 2 channels in the soma [Fig. 5 D; KT5720: μ 1 = 38 ± 5.5 pN, μ 2 = 55 ± 7 pN, μ 3 = 70 ± 8 pN, surface density = 14.01 ± 1.1%, P < 0.001; Fig.…”
Section: Resultssupporting
confidence: 49%
See 4 more Smart Citations
“…5 A ; KT5720: μ = 20 ± 5.5 pN, surface density = 9.14 ± 1.02%, P < 0.01; Fig. 5 B ; Rp‐cAMPS: μ = 20 ± 5.0 pN, surface density = 10.09 ± 1.41%, F (2, 20) = 12.27, P < 0.01]; however, we did not observe any induction of nanoclustering of K Ca 2 channels, which we had previously found (12) and confirmed again here with K Ca 2 channels in the soma [Fig. 5 D; KT5720: μ 1 = 38 ± 5.5 pN, μ 2 = 55 ± 7 pN, μ 3 = 70 ± 8 pN, surface density = 14.01 ± 1.1%, P < 0.001; Fig.…”
Section: Resultssupporting
confidence: 49%
“…We found that K Ca 2.3 is the main K Ca 2 channel subtype that is present along the AIS and is uniformly distributed in the proximal and distal AIS. We also demonstrated that basal cAMP‐PKA activity regulates the surface expression of axonal K Ca 2 channels; however, axonal K Ca 2 channels do not appear in nanoclusters in the absence of cAMP‐PKA activity, unlike their somatodendritic K Ca 2 channel counterparts (12). Furthermore, elevated PKA levels continually retrieve K Ca 2 channels from the axonal membrane in a dynamin‐independent manner.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations